Ivan Pavlov's Behavioral Counseling Effectiveness With Modeling Techniques To Improve Character Speaks Funnyly, Through Lesson Study - Karmila Jayanthi; Ketut Dharsana; Nyoman Dantes (RedwhitePress)
This study aims to determine the effectiveness of Ivan Pavlov's behavioral counseling modeling techniques to improve the character of speaking funny through lesson study. This type of research is quasi-experimental with a pre-test and post-test control group design. A sample of 20 students with df 19. The method of collecting data using character questionnaires spoke 20 funny items. The results of data analysis are ttable 70.83> tcount1,729 Ho is rejected and Ha is accepted. So there is a significant difference. It can be concluded that Ivan Pavlov's behavioral counseling is an effective modeling technique to improve character speaking with humor.